PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN (Studi Pada UD. Nealma Food Sumbawa Besar) - Roos Nana Sucihati; U Usman; Fiana Arma Yunita (Fakultas Ekonomi dan Manajemen, 2022)
This study aims to determine the effect of service quality consisting of tangibles, reliability, responsiveness, assurance and empathy on customer loyalty at UD. Nealma Food Sumbawa Besar. This type of research is associative research. Collecting data using a questionnaire method distributed to respondents. The respondents in this study amounted to 30 customers UD. Nealma Food Sumbawa Besar. Data analysis was carried out using the Partial Least Square program with the help of Smart PLS software. This research model is a reflective construct model at the second order level which consists of two stages of testing, namely testing the measurement model (outer model) and testing the structural model (inner model). The results showed that the quality of service to consumers, namely tangibles, reliability, responsiveness and assurance had no effect on customer loyalty, while empathy had a positive and significant effect on customer loyalty at UD. Nealma Food Sumbawa Besar. Changes in the customer loyalty variable can be explained well by the tangibles, reliability, responsiveness, assurance and empathy variables, which are 1,000 which means they are in the substantial/strong category.